Commemorative plaque at Flora Fountain - Ghosh, Ayan (Jio Institute, 2023)
The fountain was build from funds raised by the Esplanade Fee Fund Committee, and the total bill came to Rs. 47,000, a considerable sum of money at the time. About half of it was contributed by Seth Cursetjee Fardoonjee Parekh, who donated Rs. 20,500 from his own pocket. Member of the Parsi Panchayat, Seth Cursetjee Furdoonji Parekh was a noted shipbuilding baron, and his ships traded with Europe and China.